Persistence of Antibodies against Middle East Respiratory Syndrome Coronavirus - Daniel C. Payne; Ibrahim Iblan; Brian Rha; Sultan Alqasrawi; Aktham Haddadin; Mohannad Al Nsour; Tarek Alsanouri; Sami Sheikh Ali; Jennifer Harcourt; Congrong Miao; Azaibi Tamin; Susan I. Gerber; et al. (Emerging Infectious Diseases, 2016)
To determine how long antibodies against Middle East respiratory syndrome coronavirus persist, we measured long-term antibody responses among persons serologically positive or indeterminate after a 2012 outbreak in Jordan. Antibodies, including neutralizing antibodies, were detectable in 6 (86%) of 7 persons for at least 34 months after the outbreak.